Magnetic beads: An alternative method to enzymatic purification for SNaPshot reactions. (December 2017) - Burgos, G.; Freire-Paspuel, B.; Restrepo, T.; Camargo, M.; Ibarra, A.; Palacio, O.; Sánchez, ME.; Tejera, E.
Abstract: This work reports the novel application of magnetic bead systems as an alternative to enzymatic purifications for SBE probes up to 100 bp. The Ampure and Cleanseq (Beckman Coulter Co.) systems allowed simpler and faster purification of both multiplex amplicons (evidenced by a very low noise to signal ratio) and fluorolabeled SBE probes (whose recovery results in high intensity peaks). A standardized and detailed protocol is presented for validation in small to medium forensics and population genetics laboratories workflow.